커넥티드 카를 위한 운전자 감성추론 기반의 차량 제어 및 애플리케이션/서비스 프레임워크 - 국중진(Joongjin Kook) (전기학회 논문지 P권, 67(2), 2018)
In this paper, we determined the driver's stress and fatigue level through physiological signals of a driver in the connected car environment, accordingly designing and implementing the architecture of the connected cars' platforms needed to provide services to make the driving environments comfortable and reduce the driver's fatigue level. It includes a gateway between AVN and ECU for the vehicle control, a framework for native applications and web applications based on AVN, and a sensing device and an emotion estimation engine for application services. This paper will provide the element technologies for the connected car-based convergence services and their implementation methods, and reference models for the service design.